Smart Energy Networks Optimization Strategies for the Design and Operation - Ancona, Maria Alessandra (Bononia University Press, 2022)
Beginning with an overview of distributed generation technologies, as well as of the state of the art of District Heating (DH) networks, this book provides an insight on methods and strategies for the optimal design and management of the smart energy networks. First of all, an in-depth analysis on the thermal distribution networks is discussed, presenting a tool for the design and analysis of traditional DH and introducing the new concept of smart DH, with an in-depth analysis of the thermal prosumer role. In detail, the integration of distributed heat generators (e.g., solar thermal panels and cogenerators) into existing DH networks and the resulting thermodynamic effects are discussed. In addition, different possibilities for the design ex novo of such smart DH prosumers are presented. In addition, a focus on the optimization of the energy systems scheduling within complex (smart) energy networks is investigated, presenting a new software based on genetic algorithms and providing two case studies.